2017
DOI: 10.1049/iet-nbt.2016.0125
|View full text |Cite
|
Sign up to set email alerts
|

Green fabricated CuO nanobullets via Olea europaea leaf extract shows auspicious antimicrobial potential

Abstract: In present investigation, copper oxide (CuO) nanostructures have been prepared via green chemistry. leaf extract act as strong chelating agent for tailoring physical as well as bio-medical characteristics of CuO at the nano-size. Physical characterisation such as scanning electron microscope analysis depicts the formation of homogenised spherical shape nanoparticles (NPs) with average size of 42 nm. X-ray diffraction and Fourier transform infrared spectroscopy further confirmed the crystalline pure phase and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…Smaller size and positively charged NS can easily be attracted by negatively charged bacterial surface. This electrostatic force of attraction is quite helpful in auto-phagocytosis of NS inside the bacterial cellular environment ( Maqbool et al, 2016 , 2017 ). Normally, it has been observed that due to the presence of additional mucus layer (lipopolysaccharide), it is a tough task for any drug molecule to penetrate across it.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Smaller size and positively charged NS can easily be attracted by negatively charged bacterial surface. This electrostatic force of attraction is quite helpful in auto-phagocytosis of NS inside the bacterial cellular environment ( Maqbool et al, 2016 , 2017 ). Normally, it has been observed that due to the presence of additional mucus layer (lipopolysaccharide), it is a tough task for any drug molecule to penetrate across it.…”
Section: Discussionmentioning
confidence: 99%
“…Maximum penetration of the bacterial cell wall by NS has been observed due to opposite charges of attraction. These unique properties of multimode of actions and maximum invasion are quite helpful in developing NS as broad-spectrum antibiotics in the future ( Maqbool et al, 2017 ; Ni et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The probable applications of copper oxide nanoparticles (CuONPs) in gas sensors, waste treatment, catalysis, batteries, food preservation, high temperature superconductors, solar energy conversion, photovoltaic devices, dye removal, field emission emitters and in agriculture have been established [ 11 , 12 , 13 , 14 ]. Aside the previously mentioned usage, CuONPs showed exclusive anticancer, antimicrobial and antioxidant efficacy which renders them a promising tool for biomedical applications [ 15 , 16 ]. Different physical and chemical approaches like microwave irradiation, thermal decomposition, sol gel, colloidal thermal synthesis, sonochemical, hydrothermal, and quick precipitation have been reported for the synthesis of CuONPs with desired morphologies qualities [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…NS encloses a wide range of modern applications due to their extremely sized, tuned structure and physio‐chemical properties in agriculture industries [6, 7]. Although there are so many routes to engineer application targeted NS but plants were proved to be the best choice due to least cytotoxicity and greater biocompatibility [8]. Evolution in green chemistry had resulted in the development of traditional agriculture methodologies to modern industrial agriculture in the last decade.…”
Section: Introductionmentioning
confidence: 99%